Supporting nursing, midwifery and allied health professional teams through restorative clinical supervision. (10th November 2022) - Baldwin, Sharin; Coyne, Tracey; Kelly, Patricia
Abstract : The mental health and wellbeing of healthcare staff have been significantly affected by the demands resulting from the recent COVID-19 pandemic. Restorative supervision is a type of clinical supervision that supports reflective practice that can help build practitioners' resilience by focusing on the individual's experience, aiming to sustain their wellbeing and their motivation at work. This model has been shown to reduce stress and burnout and increase compassion satisfaction. This article discusses the implementation of a restorative clinical supervision programme used to support staff wellbeing in nursing, midwifery and allied health professional teams in a large London-based NHS trust.